"Gandhiji, I Have no Homeland": Cosmopolitan Insights from BR Ambedkar, India's Anti-Caste Campaigner and Constitutional Architect. (October 2017) - Cabrera, Luis
While the domestic political and legal thought of BR Ambedkar—champion of India's Dalits, shaper of its constitution and frequent critic of Mohandas Gandhi—has gained increasing notoriety, the international dimensions of his work have received relatively little attention. Ambedkar, in fact, staked out a distinctively universalistic approach to democratic citizenship and legitimacy which has important connections to and can inform current cosmopolitan dialogue. He rejected uncritical loyalty to the state, and he criticized presumptions of unity within states, arguing that foreigners' support for the self-determination of an "Indian people" would merely perpetuate caste oppression within the country. The latter argument provides a significant challenge to some recent nationalist and moderate cosmopolitan accounts, which reject some comprehensive universal rights claims, or suprastate political structures to support them, in the name of respecting a state's domestic culture. Furthermore, Ambedkar's thought on promoting democratic unity across linguistically and culturally diverse political units, as well as on pursuing domestic rights protections through suprastate institutions, offer valuable insights for the development of participation and accountability practices beyond the state.